2012
DOI: 10.1074/jbc.m112.340588
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Drugs Cause Release of Exosomes with Heat Shock Proteins from Human Hepatocellular Carcinoma Cells That Elicit Effective Natural Killer Cell Antitumor Responses in Vitro

Abstract: Background: Exosome is a novel secretory pathway for HSPs, which induce antitumor responses. Results: Anticancer drugs caused release of HSP-bearing exosomes by HepG2 cells and elicited efficient NK cell antitumor responses. Conclusion: Exosomes derived from hepatocellular carcinoma cell-resistant anticancer drug-treated HepG2 cells conferred superior immunogenicity in inducing HSP-specific NK cell responses. Significance: Exosomes provided a clue for finding an efficient vaccine for HCC immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
336
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(355 citation statements)
references
References 47 publications
14
336
1
4
Order By: Relevance
“…127 More recently, Li-Hong et al demonstrated that exosomes derived from resistant anticancer drug-treated Hepatocellular Carcinoma (HCC) cells conferred a higher antitumor response by inducing HSP-specific NK cell responses in vitro and suggested HSP-bearing exosomes could be used as an efficient vaccine for hepatocellular carcinoma immunotherapy. 128 In apparent contrast with these results, we discovered an immunosuppressive function of HSP70 at the surface of exosomes. We have shown that all cancer cells analyzed so far have the ability to secrete exosomes with HSP70 in their membrane while normal "non cancerous" cells do not.…”
Section: Hsp-exosomes In Cancer Therapycontrasting
confidence: 81%
“…127 More recently, Li-Hong et al demonstrated that exosomes derived from resistant anticancer drug-treated Hepatocellular Carcinoma (HCC) cells conferred a higher antitumor response by inducing HSP-specific NK cell responses in vitro and suggested HSP-bearing exosomes could be used as an efficient vaccine for hepatocellular carcinoma immunotherapy. 128 In apparent contrast with these results, we discovered an immunosuppressive function of HSP70 at the surface of exosomes. We have shown that all cancer cells analyzed so far have the ability to secrete exosomes with HSP70 in their membrane while normal "non cancerous" cells do not.…”
Section: Hsp-exosomes In Cancer Therapycontrasting
confidence: 81%
“…In the context of hepatocellular carcinoma the release of heat-shock protein chaperones from EVs was shown to act as a decoy enabling a NK cell response to be directed away from tumor cells. In contrast, in resistant cell lines these HSP bearing EVs were upregulated 46 . Circulating EVs in breast cancer similarly enable tumor growth by downregulating NK cell activity 44 .…”
Section: Evs Set the Place And Time For Neo-angiogenesismentioning
confidence: 84%
“…38 It has been reported that exosomes derived from anticancer drug-treated human HCC cells were rich in heat shock proteins, which could act as endogenous danger signals to stimulate NK cell-elicited antitumor responses in vitro. 39 However, more studies indicated that the cytotoxicity of NK cells was greatly impaired in tumor conditions.…”
Section: Polarization Of Tumor-promoting Macrophagesmentioning
confidence: 99%